Different views on ethics: how animal ethics is situated in a committee culture - Ideland, M. (Journal of medical ethics, 2009)
Research that includes non-human animal experimentation is fundamentally a dilemmatic enterprise. Humans use other animals in research to improve life for their own species. Ethical principles are established to deal with this dilemma. But despite this ethical apparatus, people who in one way or another work with animal experimentation have to interpret and understand the principles from their individual points of view. In interviews with members of Swedish animal ethics committees, different views on what the term ethics really means were articulated. For one member, the difficult ethical dilemma of animal experimentation is the lack of enriched cages for mice. For another, the ethical problem lies in regulations restraining research. A third member talks about animals’ right not to be used for human interests. These different views on “ethics” intersect once a month in the animal ethics committee meetings. There is no consensus on what constitutes the ethical problem that the members should be discussing. Therefore, personal views on what ethics means, and hierarchies among committee members, characterise the meetings. But committee traditions and priorities of interpretation as well are important to the decisions. The author discusses how “ethics” becomes situated and what implications this may have for committees’ decisions.